Moderate level platelet count might be a good prognostic indicator for intra-abdominal infection in acute pancreatitis: A retrospective cohort study of 1,363 patients - Sun, Wenwu; Huang, Jun; Ni, Tongtian; Wen, Yi; Menglu, Gui; Yongguo, Wang; Yanbin, Zhao; Sheng, Huiqiu; Chen, Ying; Ma, Li; Zhao, Bing; Mao, Enqiang (Frontiers in Medicine, 2023)
Background: Early recognition of the risk factors is important for acute pancreatitis management. The aim of this study is to investigate the relationship between platelet count and clinical outcomes in acute pancreatitis patients. Methods: The data are collected from a university-affiliated hospital between January 2013 and December 2020. A generalized additive model and a two-piecewise linear regression model are used to estimate the association between platelet count and the risk of intra-abdominal infection, surgical intervention, in-hospital mortality, and length of hospital stay. Results: Among the 1363 patients, 99 (7.3%) patients suffered intra-abdominal infection, 190 (13.9%) patients underwent surgical intervention and 38 (2.8%) patients died in the hospital. The median length of hospital stay is 21 days. Generalized additive model and two-piecewise linear regression analysis show that the risk of intra-abdominal infection decreases with the platelet count increases to 160 x 109/L (OR 0.991, 95% CI 0.984 - 0.998, p = 0.015) and then increases with the platelet count levels up (OR 1.007, 95% CI 1.004 - 1.010, p < 0.001). The trend is similar to the risk of surgical intervention and length of hospital stay. Even though there seems a declining trend in mortality, no significant association is found after adjustment for potential confounders. Further analysis shows that changes in platelet count within the first 3 days after admission have no obvious association with clinical outcomes. Conclusions: Platelet count around 160 x 109/L on admission is associated with the lowest risk of intra-abdominal infection, surgical intervention, and shortest hospital stay in acute pancreatitis patients.